Dynamics of mountain bicycles with rear suspensions: modelling and simulation - Good, C.; McPhee, J. (Sports Engineering, 1999)
A dynamic model of a rider on a rear-suspension mountain bicycle is presented. By combining the rider, main frame and crank into a single rigid body, the need for determining interface loads between the rider, seat, handlebars and pedals is eliminated. The only excitation to this relatively simple model is the chain tension force as a function of crank angle. The equations of motion are obtained in symbolic form using Maple algorithms and a linear graph representation of the system. The resulting equations are solved numerically in order to simulate the bicycle being ridden up a smooth 6% grade. The simulation results are in good agreement with those obtained from a more complex model, and clearly show the pedal-induced oscillations of the rear suspension.